H-bonded reusable template assisted para-selective ketonisation using soft electrophilic vinyl ethers - Arun Maji (Nature Portfolio, 2018)
Electrophilic acylation of arenes is largely limited to electron rich systems, non-polar medium and often displays moderate selectivity. Here, the authors show a directed para-selective ketonisation of arenes, overriding electronic bias and structural congestion, and apply it to the synthesis of bioactive compounds.